Interaction between the 4G - EPC core and the 5G RAN - Pasarelski, Rosen; Angelov, Krasen (Yearbook Telecommunications, 2024)
The Radio Access Network - 5G RAN is designed to work seamlessly with the existing 4G EPC network infrastructure. This enables a smooth transition from fourth 4G to fifth generation 5G mobile systems, both for operators and end users. The radio access network - 5G RAN uses a new core network architecture - 5GC, which is designed to be more flexible and scalable than the previous EPC architecture. The purpose of writing the article is to analyze the methods of interaction between the EPC core of 4G networks and the 5G system core. To explore interfaces and interconnection protocols with an emphasis on roaming and non-roaming architectural models. To discuss the interaction between the 5GC core network and the E-UTRAN radio network associated with the EPC in terms of achieving this goal through non-3GPP access. Analysis of the methods of interaction between the EPC core of 4G networks and the 5GС, the study of interfaces and interaction protocols in different operating environments can be noted as contributions to the development of the article.